Pengaruh Digital Marketing, Perilaku Konsumen Dan Kepuasan Konsumen Terhadap Loyalitas Konsumen (Studi Kasus Konsumen Equal Coffee) - Hermawan, Gugus; Rizal, Mohammad; Utama, Satria Putra (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to examine and determine the influence of Digital Marketing, Consumer Behavior, and Consumer Satisfaction on Consumer Loyalty (A Case Study of Equal  Coffee Consumers). This research is a quantitative study. The sampling technique was carried out using Lemeshow’s formula, resulting in a total of 90 samples. The data used in this study is primary data obtained by distributing questionnaires to visitors of Equal  Coffee Malang. To address the research problem, SPSS was utilized, employing instrument tests such as validity and reliability tests, normality tests, classical assumption tests including multicollinearity and heteroscedasticity tests, multiple linear regression analysis, and hypothesis testing using the F-test, t-test, and the coefficient of determination test. The results of this study indicate that Digital Marketing has a significant positive effect on Consumer Loyalty, Consumer Behavior has a significant positive effect on Consumer Loyalty, and Consumer Behavior has a significant positive effect on Consumer Loyalty. Keywords: Digital Marketing, Consumer Behavior, Consumer Satisfaction, Consumer Loyalty